Aesthetic approach for anterior teeth with enamel hypoplasia - Josué Martos; Andréa Gewehr; Emanuele Paim (Wolters Kluwer Medknow Publications, 2012)
Enamel hypoplasia is a developmental defect of the enamel that is produced by a disturbance in the formation of the organic enamel matrix, clinically visible as enamel defects. Disorders that occur during the stages of enamel development and maturation reduce the amount or thickness of the enamel, resulting in white spots, tiny grooves, depressions and fissures in the enamel surface. The complexity and intensity of the dental deformity lesions will conduct the ideal treatment-associating conservative techniques. This article presents a case report of a restorative treatment of enamel hypoplasia using hybrid composite resin to mask color alteration and enamel defects. An aesthetic appearance that respects the tooth polychromatic and the self-esteem of the patient can be achieved with this approach.